ANALYSIS OF FINANCIAL STATEMENTS SD NURUL HUDA II SURABAYA REVIEWED FROM PSAK NO.1 (PRESENTATION OF FINANCIAL STATEMENTS) - Nur Fadilah; Hamdan, Ali (Ekosiana Jurnal Ekonomi Syari ah, 2017)
The financial report is the final product of the accounting process of an entity that becomes information material for the users as one of the ingredients in the decision making process.The purpose of this study is to compare the presentation of financial statements in the financial statements of SD Nurul Huda II with financial statements that are in accordance with PSAK No.1. The method used is a qualitative research method with a descriptive approach, which describes the theory contained in PSAK No.1 concerning the presentation of financial statements at SD Nurul Huda II.The results of the study show that the financial statements of SD Nurul Huda II present financial statements according to the rules and methods that have been applied at the Nurul Huda Foundation. That consists of the time and components of making financial statements. In other words, the financial statements at SD Nurul Huda II are not in accordance with PSAK No.1 (financial statement presentation) Keywords: Financial Report, Psak No.1